2022
DOI: 10.48550/arxiv.2203.07422
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Bayesian-EUCLID: discovering hyperelastic material laws with uncertainties

Akshay Joshi,
Prakash Thakolkaran,
Yiwen Zheng
et al.

Abstract: Within the scope of our recent approach for Efficient Unsupervised Constitutive Law Identification and Discovery (EUCLID), we propose an unsupervised Bayesian learning framework for discovery of parsimonious and interpretable constitutive laws with quantifiable uncertainties. As in deterministic EUCLID, we do not resort to stress data, but only to realistically measurable full-field displacement and global reaction force data; as opposed to calibration of an a priori assumed model, we start with a constitutive… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 68 publications
0
5
0
Order By: Relevance
“…Identification of micromechanical parameters within the multiscale regime has been experimentally performed by Fedele et al (2006), where differences between the experimentally observed homogenized stress field and predictions from numerical simulations carried out on a representative volume were minimized, assuming certain micromechanical parameters to be known a priori. Finally, parameter identification within the probabilistic realm, e.g., Rappel et al (2020), Hu et al (2016), Oskay and Fish (2008), and Rosić et al (2013), and machine learning realm, e.g., Flaschel et al (2021Flaschel et al ( , 2022, Joshi et al (2022), have been discussed as well.…”
Section: Introductionmentioning
confidence: 99%
“…Identification of micromechanical parameters within the multiscale regime has been experimentally performed by Fedele et al (2006), where differences between the experimentally observed homogenized stress field and predictions from numerical simulations carried out on a representative volume were minimized, assuming certain micromechanical parameters to be known a priori. Finally, parameter identification within the probabilistic realm, e.g., Rappel et al (2020), Hu et al (2016), Oskay and Fish (2008), and Rosić et al (2013), and machine learning realm, e.g., Flaschel et al (2021Flaschel et al ( , 2022, Joshi et al (2022), have been discussed as well.…”
Section: Introductionmentioning
confidence: 99%
“…Later, De Lorentzis and co-workers [13,14] utilized sparse regression to discover interpretable constitutive laws for a wide array of material classes. An interesting extension to this work was the development of an unsupervised Bayesian framework for discovering hyperelasticity models which accounts for uncertainty [15]. Neural networks and Gaussian process models have been widely employed as replacements for human-selected, traditional model forms.…”
Section: Introductionmentioning
confidence: 99%
“…In the (material) model-free paradigm proposed by Kirchdoerfer and Ortiz (2016) and first formulated for elasticity, a material's state of deformation is directly mapped to a stress state closest to the stress-strain pair available in the dataset (subject to physical compatibility constraints) (Kirchdoerfer and Ortiz, 2016;Ibañez et al, 2017;Kirchdoerfer and Ortiz, 2017;Conti et al, 2018;Nguyen and Keip, 2018;Eggersmann et al, 2019;Carrara et al, 2020;Karapiperis et al, 2021). Alternative approaches keep the concept of a material model and surrogate it by learning an approximate mapping between the strains and stresses (referring again to the easiest case of elasticity) using, e.g., sparse regression with feature engineering (Flaschel et al, 2021(Flaschel et al, , 2022Joshi et al, 2022;Wang et al, 2021), manifold learning methods and polynomial approximations (Ibañez et al, 2018(Ibañez et al, , 2017González et al, 2019b), Gaussian process regression (Rocha et al, 2021;Fuhg et al, 2022), and artificial neural networks (NNs) (Ghaboussi et al, 1991;Fernández et al, 2021;Klein et al, 2022;Vlassis and Sun, 2021;Kumar et al, 2020;Bastek et al, 2022;Zheng et al, 2021;Mozaffar et al, 2019;Bonatti and Mohr, 2021;Vlassis et al, 2020;Kumar and Kochmann, 2021;As'ad et al, 2022;Liang et al, 2022), with the list being roughly in order of decreasing physical interpretability and increasing approximation power. Further hybrid approaches use data to construct automatic corrections to existing models (Ibáñez et al, 2019;González et al, 2019a).…”
Section: Introductionmentioning
confidence: 99%
“…To address the aforementioned limitations of classical approaches and supervised data-driven methods, the authors recently proposed a novel framework denoted as Efficient Unsupervised Constitutive Law Identification and Discovery (EUCLID) (Flaschel et al, 2021(Flaschel et al, , 2022Joshi et al, 2022). The method is unsupervised, i.e., it requires no stress data but only global reaction forces and full-field displacement data realistically obtainable through, e.g., DIC or DVC; it uses sparse regression over a large catalog of candidate functions to deliver interpretable constitutive laws given by parsimonious mathematical expressions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation